Case report: Pneumonia with clinical symptoms precedes imaging evidence after immune checkpoint inhibitors combined with radiotherapy in lung squamous cell cancer - Wang, Yao; Wang, Yimeng; Yu, Jinming; Meng, Xiangjiao (Frontiers in Immunology, 2022)
Immune-checkpoint inhibitors (ICI) targeting programmed cell death 1 (PD-1) and its ligand 1 (PD-L1) inhibitors have quickly changed the treatment landscape in advanced non-small cell lung cancer. However, any patient treated with an immune checkpoint inhibitor is at risk for immune-related adverse events (irAEs). Checkpoint inhibitor pneumonitis (CIP) is rare but potentially severe pulmonary toxicity of immunotherapies. The diagnosis of CIP is often challenging, as imaging features and symptoms are not specific and may mimic other lung diseases, thus potentially delaying appropriate patient management. In this setting, a comprehensive understanding of imaging features is essential for a prompt detection and correct management of these drug-induced lung diseases. We presented a patient with lung squamous cell cancer who has clinical symptoms precede imaging evidence of pneumonia after immunotherapy and radiotherapy. We also discussed the safety of immunotherapy, the complexity and management of immune pneumonitis.